2021
DOI: 10.4081/monaldi.2021.1623
|View full text |Cite
|
Sign up to set email alerts
|

Awake prone positioning in non-intubated patients for the management of hypoxemia in COVID-19: A systematic review and meta-analysis

Abstract: Coronavirus disease-2019 (COVID-19) may lead to hypoxemia, requiring intensive care in many patients. Awake prone positioning (PP) is reported to improve oxygenation and is a relatively safe modality. We performed a systematic review of the literature to evaluate the available evidence and performed meta-analysis of the effect of awake PP in non-intubated patients on improvement in oxygenation and reducing the need for intubation. We searched the PubMed and EMBASE databases to identify studies using awake PP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…The added value of the present meta-analysis lies on the (i) analysis of both raw (the largest so far database with peerreviewed data) and aggregate data, and (ii) use of strict methodological criteria (only crossover studies) and sensitivity analyses performed separately in awake and intubated patients. Two relevant meta-analyses were recently published presenting consistent findings (47,48). However, these analyses included studies only in awake patients, as well as both peer-reviewed and non-peer-reviewed studies or studies employing either crossover or parallel arm design (47,48).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The added value of the present meta-analysis lies on the (i) analysis of both raw (the largest so far database with peerreviewed data) and aggregate data, and (ii) use of strict methodological criteria (only crossover studies) and sensitivity analyses performed separately in awake and intubated patients. Two relevant meta-analyses were recently published presenting consistent findings (47,48). However, these analyses included studies only in awake patients, as well as both peer-reviewed and non-peer-reviewed studies or studies employing either crossover or parallel arm design (47,48).…”
Section: Discussionmentioning
confidence: 97%
“…Two relevant meta-analyses were recently published presenting consistent findings (47,48). However, these analyses included studies only in awake patients, as well as both peer-reviewed and non-peer-reviewed studies or studies employing either crossover or parallel arm design (47,48). The latter constitutes a criterion with high clinical relevance since in crossover studies each patient serves as a control of her/his own.…”
Section: Discussionmentioning
confidence: 99%
“…Prone position is a position in which the patient is treated by remaining prone without endotracheal intubation. Some studies have found that for severe patients, prone position combined with mask oxygen or HFNC or non-invasive positive pressure ventilation can reduce the probability of endotracheal intubation and ultimately reduce patient mortality [38][39][40][41][42]. Other studies have shown that prone position may be more effective when performed early than later [10,43].…”
Section: Discussionmentioning
confidence: 99%
“…[ 59 ] A meta-analysis on awake proning in nonintubated COVID-19 patients also showed significant improvement in PaO 2 : FiO 2 ratio, SpO 2, and PaO 2 . [ 60 ]…”
Section: Managementmentioning
confidence: 99%